Japanese Management Accounting: A World Class Approach to Profit Management (Book). - Moriarity, Shane R.; Poston, Kay M. (The Accounting Review, 1991)
Abstract Reviews the book "Japanese Management Accounting: A World Class Approach to Profit Management," by Yasuhiro Monden and Michiharu Sakurai.